Transition to adult care for young people with cerebral palsy. (February 2020) - Myers, Lisa L.; Nerminathan, Arany; Fitzgerald, Dominic A.; Chien, Jimmy; Middleton, Anna; Waugh, Mary-Clare; Paget, Simon Paul
Abstract: Cerebral palsy (CP) is associated with a high burden of comorbid respiratory disease subsequent to multiple risk factors associated with increasing levels of disability. Correspondingly, respiratory disease is the leading cause of death in CP, including amongst young people who are transitioning or who have just transitioned between paediatric and adult healthcare services. Therefore, consideration of both preventive and therapeutic respiratory management is integral to transition in patients with CP, as summarised in this review.